Identification and characterization of esterase producing microbes from dairy sludge through metagenomic approach - Abeesh P (Department of plant biotechnology, College of agriculture, 2014)
The study entitled “Identification and characterization of esterase producing microbes from dairy sludge through metagenomic approach” was conducted at the Department of Plant Biotechnology, College of Agriculture, Vellayani, Thiruvananthapuram during 2013-2014. The objective of the study was to construct and characterize metagenomic library for esterase producing microbes from dairy sludge. The dairy sludge samples were collected from the outlet of waste water treatment plant of MILMA (Kerala Co-operative Milk Marketing Federation) unit, Ambalathara, Thiruvananthapuram. Three protocols were tried for the isolation, out of which the protocol of Singka et al. (2012), which combines mechanical and chemical lysis, was found to be the best. This protocol was modified by increasing the concentration of NaCl, to optimize it for dairy sludge, which contained polysaccharides and humic acids as contaminants. The modified protocol yielded good DNA in terms of quality (A260/A280 of 1.784) and quantity (11.4 µg/g). For metagenomic library constriction, the DNA was digested using restriction enzyme Hpa I (Haemophilus parainfluenzae I) and the fragments obtained after 1 and 2 h were cloned in to pEZ BAC vector using clone smart ligase of Lucigen (USA). The Blue white screening system, along with selection based on chloramphenicol resistance, yielded eighty two transformed colonies. Functional screening of the library on tributyrin agar plates could identify 24 esterase positive clones. Estimation of enzyme activity of ten selected clones showed the maximum activity of 8.942 U/mg protein. Agarose gel electrophoresis of the vector DNA isolated from ten selected esterase positive clones showed the presence of metagenome insert. Inserts of size more than 3 Kb could be amplified from the five esterase positive clones.